Feminist pedagogy and adult learning : Underlying theory and emancipatory practice - Elizabeth J. Tisdell (Adult Education Research Conference, 1996)
This paper examines the theoretical underpinnings of various trends of feminist pedagogy and its relationship to adult learning around issues of the construction of knowledge, authority, voice, and dealing with difference.